Characterization of the Unsaponifiable Fraction of Oils from the Pulp of Safous South in West of Democratic Republic of Congo - Mayele Kipoy David; Gindo M. V.G.; Tshiombe Mulumba Van; Kakolongo Tumba Joséphine (Britain International of Exact Sciences (BIoEx) Journal, 2023)
The unsaponifiable fraction of oils from the pulp of safous was characterized through the study of essential oils and phytosterols. The essential oils found in the samples of the three zones showed qualitatively, the following composition: α-pinene, β-pinene, α-phellandrine, Benzene-1-methyl, phellandrene, 3-carene, caryophyllene. While higher alcohols and phytosterols found in the unsaponifiable Kinshasa were the 1-eicosanol, 1-Tétracosanol, 5-α-cholestane, 1-hexacosanol, 1-octacosanol, cholesterol, campesterol, Stigmasterol-1, 1-triacontanol, the β-sitosterol, and stigmastanol.